A New Timber Species of Amanoa (Phyllanthaceae; Phyllanthoideae) Endemic to Colombia’s Montane Forests and Critically Endangered, with an Updated Key for the Species of the Genus - Villanueva-Tamayo, Boris; Bravo, Lina M. Corrales; Aymard-Corredor, Gerardo A. (Phytotaxa, 2024)
Amanoa tolimensis, a critically endangered new timber tree species from Andean forests of Colombia is described, illustrated, and its distinctive morphological structures are displayed through a Lankester plate. A. tolimensis is recorded so far in montane forests over sandy-clay soils of “Bosque de Galilea” Regional Natural Park, an area located on the western flank of the eastern mountain range of Tolima department. This new species belongs to a small group within the genus characterized by the presence of an androphore, and presents morphological similarities with A. almenrindae. The latter, is a shrub to small tree from black water periodically flooded forests and savannas of Rio Negro basin of Brazil, Colombia and Venezuela. This new species is a tree 24 m tall, with branches and inflorescence lenticellate, with a ferruginuous tomentum, presenting differences in shape and size in leaves, petioles, pedicels, sepals, ovary, and the pistillate flowers are pedicellate. Additionally, habitat, phytogeographical information, a distribution map, and data about its conservation status are included. An updated identification key for the neotropical species of Amanoa is also provided. This new species represents the first report of this genus in Colombian Andes, and the first endemism of this genus for the country. Amanoa tolimensis is under pressure from logging in some areas of the park, and urgent protection of the species is needed.